Targeting Parenting Quality to Reduce Early Life Adversity Impacts on Lifespan Cardiometabolic Risk - Bleil, Maria E.; Spieker, Susan J.; Booth-LaForce, Cathryn (Frontiers in Psychology, 2021)
Mounting evidence that early life adversity (ELA) exposures confer risk for cardiometabolic disease over the lifespan motivated this narrative review to examine parenting quality as a potential intervention target to reduce ELA exposures or mitigate their impact as a way of reducing or preventing cardiometabolic disease. We describe findings from the limited number of family-based intervention studies in ELA-exposed children that have tested parenting impacts on cardiometabolic health outcomes. We then describe the implications of this work and make recommendations for future research that will move this field forward.